Simultaneous non-union of scaphoid and capitate: a case report - Fukushi, Ryunosuke (Case Reports Plast Surg Hand Surg, 2019)
A 44-year-old painter separately developed simultaneous nonunions at the middle of the capitate and distal third of the scaphoid, for which we performed a cancellous bone graft from the iliac crest and a pedicled 1,2-intercompartmental supraretinacular artery graft, respectively. Union of both bones was ultimately achieved.